Theatre and the quantum world - Kornienko, Nelly (Opción, 2019)
The article develops ideas of a new approach we have initiated – the synergetics of artistic culture (theater), in particular, problems related to nonlinear systems. As a method, subconscious patterns are explored under the theme of Theatre and the Quantum World. In result, the evolution of an ascent to a new artistic complexity occurs with iterations of meaningful senses at relevant levels of artistic space organization. As a conclusion, the iteration accumulates in an upward progression on several levels, with an essential loss of energy occurring at the dissipation stage.